Exploring classroom-based assessment for young EFL learners in the Chinese context: Teachers’ beliefs and practices - Yan, Qiaozhen; Zhang, Lawrence Jun; Dixon, Helen R. (Frontiers in Psychology, 2022)
Classroom-based assessment (CBA) is an approach for learning improvement that has been advocated as having strong potential in enhancing learner autonomy of young language learners (YLLs). This study investigated Chinese primary school English as a foreign language (EFL) teachers’ beliefs about CBA, their assessment practices, and the relationship between their CBA beliefs and practices. Drawing on data from a survey of 195 Chinese primary school EFL teachers, results showed that the teachers positively believed in the value of various CBA processes, including planning assessment, collecting learning evidence, making professional judgments and providing appropriate feedback, and they also attempted to enact these assessment practices; belief-practice alignment was also identified, showing that teachers’ beliefs about CBA were significant predictors of their assessment practices. Implications are provided for promoting the implementation of CBA for YLLs in similar contexts.